Bridging Revelation and Reality: Pedagogical Reform in Islamic Education through the Lens of Fazlur Rahman - Edi Sutrisno; Taufikin (Al-Qalam Institute, 2025)
This study aims to analyze the implementation model of Fazlur Rahman's thought in the development of modern Islamic vocational education. The primary focus of this study is how the integration between general science and religious science is realized systematically through curriculum, learning, and school culture. A descriptive qualitative approach is used, with data collected through interviews, observations, and documentation. The results of the study show that SMK NU Gembong has successfully applied Rahman's idea of integrating knowledge by removing the dichotomy between religious and general knowledge. This merger is evident in the curriculum, which includes tafsir, hadith, nahwu, fiqh, and Ke-NU-an, alongside vocational lessons in computers, automotive, and accounting. In addition, Rahman's concept of double movement is adapted in the learning of tafsir and hadith, where students are trained to understand the historical context of verses and relate them to modern reality. This implementation not only strengthens students' technical competence but also fosters moral and spiritual character rooted in Islamic values. This research emphasizes that Islamic vocational education can serve as a laboratory for integrating knowledge relevant to modern needs while maintaining the integrity of Islamic values.